EKSPLORASI KAPABILITAS ODOO ERP MODUL HR DALAM MENDUKUNG OPERASIONAL SUMBER DAYA MANUSIA DI BANK ACEH SYARIAH - M.Rifqi Ghifari; Nur Wijayaning Rahayu (Journal of Information System, Informatics and Computing, 2026)
In the digital era, the banking industry requires integrated information systems to maintain operational efficiency. This study aims to explore the capabilities of the Odoo ERP HR module in supporting personnel operations at Bank Aceh Syariah, which currently faces challenges such as manual processes, data redundancy, and technical "time-out" errors during payroll processing. The research method used is descriptive qualitative through literature studies and in-depth interviews with staff from the Human Capital Division at Bank Aceh Syariah. The exploration results indicate that Odoo's module capabilities are able to comprehensively address four main system requirements, namely integrated employee data management, transparent attendance recording, transparent performance appraisal, and optimized payroll processing. The Employees module serves as a Single Source of Truth for employee identity and contract data. The Attendance and Time Off modules provide real-time attendance and leave data. The Project module records task-based productivity, while the Appraisal module provides objective performance evaluation. All of this data is automatically integrated into the Payroll module, which is capable of performing instant and transparent salary calculations. This study concludes that the implementation of Odoo ERP has the potential to overcome data fragmentation, minimize inter-unit mutation mismatches, reduce dependence on manual reconciliation, and support a more stable and accurate payroll process at Bank Aceh Syariah